Extracranial carotid plaque calcification and its association with risk factors for cerebrovascular events: insights from the ANTIQUE study - Pakizer, David; Šalounová, Dana; Školoudík, David (Frontiers in Neurology, 2025)
IntroductionExtracranial carotid calcification is a common marker of advanced atherosclerosis. However, its impact on stroke risk is not consistent across studies, and examining the type of calcification and the presence of systemic diseases might be helpful. We aimed to investigate extracranial carotid calcification and its association with risk factors for ischemic cerebrovascular diseases.Materials and methodsAmong 1,863 consecutive patients in the Atherosclerotic Plaque Characteristics Associated with a Progression Rate of the Plaque and a Risk of Stroke in Patients with the Carotid Bifurcation Plaque Study (ANTIQUE), 132 symptomatic or asymptomatic patients (177 carotid plaques) with >30% carotid stenosis examined through computed tomography (CT) and magnetic resonance imaging (MRI) were included. Statistical data were assessed using the χ2-test, Fisher’s exact test, t-test, and Mann–Whitney test to investigate the calcification risk factors.ResultsCompared to the absence of calcifications, spotty calcifications were associated with male sex [odds ratio (OR): 3.72, 95% confidence interval (CI): 1.06–13.05], while large calcifications were associated with older patients (OR: 1.60 per 5 years of age, 95% CI: 1.20–2.13). Large calcifications were also strongly associated with coronary heart disease (OR: 4.07, 95% CI: 1.15–14.44) and atrial fibrillation (p = 0.025). In comparison between only spotty and large calcifications, spotty calcifications were associated with male sex (OR: 3.72, 95% CI: 1.06–13.05), smoking (p = 0.020) in more significant quantities (p = 0.014), and lipid plaque (p < 0.001), while large calcifications with contralateral stenosis degree (p = 0.044). No significant relationship was found between cerebrovascular events and the type of calcification.ConclusionAlthough the presence and type of extracranial carotid calcification were not related to ipsilateral ischemic events, large calcifications were strongly associated with coronary heart disease and atrial fibrillation.Clinical trial registrationClinicalTrials.gov, identifier NCT02360137.